Effect of valproic acid on extrinsic and intrinsic apoptotic pathways, cell viability and apoptosis in hepatocellular carcinoma PLC/PRF5 cell line: Valproic acid effects on hepatocellular carcinoma cells - Lu, Yan; Liu, Yao; Zhang, Ke; Jiang, Li (Cellular and Molecular Biology, 2022)
Inhibitors of histone deacetylase enzymes induce various molecular and extracellular effects that lead to their anticancer role. In this study, the result of valproic acid on the expression of genes of extrinsic pathway and intrinsic pathway of apoptosis, cell viability, and apoptosis in liver cancer PLC/PRF5 cell line was designed. For this purpose, PLC/PRF5 liver cancer cells were cultured, and after the overlapping of the cells reached about 80%, the cells were collected with trypsin and after washing, they were cultured on a plate with a concentration of 3 x 105. After 24 hours, the culture medium was treated with a medium containing valproic acid (the control group received only DMSO). 24, 48, and 72 hours after treatment to determine the cell viability, apoptotic cells, gene expression, MTT, flow cytometry, and Real-time techniques. The results showed that valproic acid significantly inhibited cell growth, induced apoptosis, and decreased the expression of Bcl-2 and Bcl-xL genes. Also, it increased the expression of DR4, DR5, FAS, FAS-L, TRAIL, BAX, BAK, and APAF1 genes. In general, valproic acid seems to play its apoptotic role through intrinsic and extrinsic pathways in liver cancer.